2023
DOI: 10.1186/s12905-023-02230-5
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing reproductive and abortion care barriers: findings on the student health center's role from a student survey

Abstract: Background College-aged young adults in the US have low utilization and high need for reproductive healthcare. Multiple barriers to reproductive care exist. University Student Health Centers (SHCs) provide varying degrees of reproductive products and services. Recently, California legislated that public university SHCs add medication abortion to their care. Methods To examine existing attitudes and barriers to reproductive healthcare for public un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
2
1
0
Order By: Relevance
“…Finally, the availability of Just in Case increased students’ perception of access to over-the-counter emergency contraceptives on campus, with a 28% increase in post-survey respondents who indicated “Easy Access.” There was also a change in those participants who responded to having “Minimum Access” and “No Access.” The availability of products in Just in Case and the connected health promotion and education activities comprising this larger initiative likely shaped this change in response. This finding supports previous research studies showing that college and university students prefer access to contraception and sexual health resources via a comfortable environment [ 43 , 50 ] and discreet ways [ 20 , 21 , 51 ]. When implementing a mail-order contraceptive delivery program for college students, Butler and colleagues [ 52 – 54 ] found that receiving condoms and other sexual health aids via this modality allowed more discretion than a traditional campus health center setup, which in turn increased students’ ease when ordering sexual health supplies while decreasing high-risk behaviors via increased condom usage.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Finally, the availability of Just in Case increased students’ perception of access to over-the-counter emergency contraceptives on campus, with a 28% increase in post-survey respondents who indicated “Easy Access.” There was also a change in those participants who responded to having “Minimum Access” and “No Access.” The availability of products in Just in Case and the connected health promotion and education activities comprising this larger initiative likely shaped this change in response. This finding supports previous research studies showing that college and university students prefer access to contraception and sexual health resources via a comfortable environment [ 43 , 50 ] and discreet ways [ 20 , 21 , 51 ]. When implementing a mail-order contraceptive delivery program for college students, Butler and colleagues [ 52 – 54 ] found that receiving condoms and other sexual health aids via this modality allowed more discretion than a traditional campus health center setup, which in turn increased students’ ease when ordering sexual health supplies while decreasing high-risk behaviors via increased condom usage.…”
Section: Discussionsupporting
confidence: 91%
“…Studies have stressed the importance of health centers in college and university settings in reducing sexual health disparities in student populations [ 20 ]. Students are more likely to visit a university health care center for their sexual health and family planning needs than other settings [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The availability of products in The Kit and the connected health promotion and education activities comprising this larger initiative will likely have shaped this change in response. This nding supports previous research studies showing that college and university students prefer access to contraception and sexual health resources via a comfortable environment [38,45] and discreet ways [20,21,46]. When implementing a mail-order contraceptive delivery program for college students, Butler and colleagues [47][48][49] found that receiving condoms and other sexual health aids via this modality allowed more discretion than a traditional campus health center setup, which in turn increased students' ease when ordering sexual health supplies while decreasing high-risk behaviors via increased condom usage.…”
Section: Discussionsupporting
confidence: 90%